Effect of choline chloride premedication on xylazine-induced hypoxaemia in sheep. (September 2017) - Singh, Preet M.; Reid, Katherine; Gaddam, Ravindra; Bhatia, Madhav; Smith, Stefan; Jacob, Antony; Chambers, Paul
Abstract: Objective: To determine the anti-inflammatory efficacy of choline in vivo and in vitro and to investigate the anti-inflammatory mechanisms of choline. Study design: Randomized, controlled studies. Animals: In vivo trials used 16 Romney sheep. In vitro experiments utilized RAW 264.7 mouse macrophage cells. Methods: Hypoxaemia induced in 16 sheep by intravenous (IV) injection of 50 μg kg –1 xylazine, an α-2 agonist, was measured in sheep at 0, 1 and 4 minutes using arterial blood gas analysis with and without 50 mg kg –1 IV choline chloride premedication. Cell culture studies used enzyme-linked immunosorbent assay to measure the release of tumour necrosis factor (TNF-α) from lipopolysaccharide (LPS) stimulated macrophages with and without choline chloride premedication. TNF-α release was compared to thalidomide suppressed and untreated cells. Results: Choline premedication in sheep mitigated a reduction in arterial partial pressure of oxygen (PaO2 ) but did not prevent development of clinically significant hypoxaemia. Decrease in mean PaO2 of choline treated sheep was 6.36 kPa (47.7 mmHg) compared to 9.81 kPa (73.6 mmHg) in control sheep. In vitro studies demonstrate that choline administered concurrent with LPS activation did not significantly suppress TNF-α expression but that treatment of cells with choline 10 minutes prior to LPS activation did significantly suppress TNF-α expression. Choline pretreated cells expressed 23.99 ± 4.52 ng mg –1 TNF-α while LPS only control cells expressed 33.83 ± 3.20 ng mg –1 . Conclusions: Choline is able to prevent macrophage activation in vitro when administered prior to LPS activation and may reduce hypoxaemia in sheep developing pulmonary oedema after xylazine administration. This effect requires premedication with choline. Clinical relevance: Pharmacological manipulation of autonomic inflammatory responses holds promise for the treatment of inflammation. However, the complex cellular mechanisms involved in this reflex means that an adequate therapy should approach multiple pathways and mechanisms of the inflammatory response.